Effect of polyhalite on growth and yield of wheat (Triticum aestivum) in India - KUMAR, VIPIN; SHEKHAWAT, KAPILA; K SINGH, RAJIV; SINGH RATHORE, SANJAY; K UPADHYAY, PRAVIN; Kumar, Sandeep (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted at ICAR-Indian Agricultural Research Institute, New Delhi, Research Farm during winter (rabi) season 2021–22 to evaluate the effect of multi-nutrient carrier polyhalite and its combinations with variable doses of MOP on growth parameters, yield, and productivity of wheat. The application of 100% K (polyhalite), i.e. T8 resulted in significantly higher growth and yield parameters of wheat, viz. plant height, dry matter accumulation, tillers numbers, crop growth rate, leaf area index, grain yield (5.87 tonnes/ha). A 7.5% increase in grain yield was observed with the application of T8 over T11. So, a balanced and prolonged supply of available nutrients with polyhalite to crop in a sustained manner can be maintained.